Evidence of beta cell dysfunction which does not lead on to diabetes: a study of identical twins of insulin dependent diabetics. Issue 6565 (17th January 1987) - Heaton, D A; Millward, B A; Gray, P; Tun, Y; Hales, C N; Pyke, D A; Leslie, R D
Abstract : Ten non-diabetic identical twins of insulin dependent diabetics were studied to see whether they showed changes in insulin secretion. The twins were selected because more than 11 years had elapsed since the diagnosis of the diabetic twin and they were therefore unlikely to develop diabetes, and they had had islet cell antibodies. Despite similar glucose concentrations to the controls the twins had greater total immunoreactive insulin responses to both oral (mean 3280 (SD 699) versus 2338 (1110) pmol/dl at 180 minutes; p less than 0.05) and intravenous (1346 (690) versus 699 (294) pmol/dl at 30 minutes; p less than 0.05) glucose challenge. The C peptide responses to intravenous glucose were also increased consistent with increased insulin secretion. In addition, basal serum proinsulin concentrations in the twins were increased (2.1 (1.2) versus 1.0 (0.3) pmol/dl; p less than 0.01) and remained so throughout both tests. These twins, who were unlikely to develop insulin dependent diabetes, showed evidence of beta cell dysfunction which does not progress to diabetes.